Teaching English in Rural Areas: A Closer Look into Teachers’ Challenges - Herizal, Herizal; Marzulina, Lenny; Erlina, Dian; Holandyah, Muhammad; Putri, Hikmah Zalifah; Amelia, Budi Arsih (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
Teaching English in rural areas remains several significant challenges. This study aimed to explore the challenges encountered by English teachers in South Sumatera, Indonesia when teaching in such environments. The research design employed for this investigation was qualitative, utilizing a case study approach. Two English language teachers from the specified region participated in this study. The research data were gathered through semi-structured interviews with open-ended questions. Subsequently, the interview data were analyzed using thematic analysis. This research revealed six distinct challenges faced by the teachers in teaching English. These challenges include: (1) inadequate infrastructure, (2) insufficient learning facilities, (3) inadequate learning resources, (4) low proficiency in English, (5) unfavorable teaching conditions, and (6) limited opportunities for teacher development. Addressing these challenges is crucial to create a positive environment for effective teaching and learning English in rural areas.